Determination of Fatty Acid Metabolism with Dynamic [C]Palmitate Positron Emission Tomography of Mouse Heart In Vivo - Yinlin Li; Tao Huang; Xinyue Zhang; Min Zhong; Natalie N. Walker; Jiang He; Stuart S. Berr; Susanna R. Keller; Bijoy K. Kundu (Molecular Imaging)
The goal of this study was to establish a quantitative method for measuring fatty acid (FA) metabolism with partial volume (PV) and spill-over (SP) corrections using dynamic [ 11 C]palmitate positron emission tomographic (PET) images of mouse heart in vivo. Twenty-minute dynamic [ 11 C]palmitate PET scans of four 18- to 20-week-old male C57BL/6 mice under isoflurane anesthesia were performed using a Focus F-120 PET scanner. A model-corrected blood input function, by which the input function with SP and PV corrections and the metabolic rate constants (k 1 –k 5 ) are simultaneously estimated from the dynamic [ 11 C]palmitate PET images of mouse hearts in a four-compartment tracer kinetic model, was used to determine rates of myocardial fatty acid oxidation (MFAO), myocardial FA esterification, myocardial FA use, and myocardial FA uptake. The MFAO thus measured in C57BL/6 mice was 375.03 ± 43.83 nmol/min/g. This compares well to the MFAO measured in perfused working C57BL/6 mouse hearts ex vivo of about 350 nmol/g/min and 400 nmol/min/g. FA metabolism was measured for the first time in mouse heart in vivo using dynamic [ 11 C]palmitate PET in a four-compartment tracer kinetic model. MFAO obtained with this model was validated by results previously obtained with mouse hearts ex vivo.